Enhancing Seventh-Grade Students’ Short Story Writing Competence through the Classroom Action Research Approach (Journal of Social And Education Research, 2024)
Writing skills are one of the essential basic competencies in developing students’ communication abilities, creativity, and critical thinking. However, observations show that many seventh-grade students struggle to write short stories in a systematic and engaging manner due to low motivation, limited vocabulary, and less interactive teaching methods. This study aims to improve the short story writing skills of seventh-grade students through the application of the Classroom Action Research (CAR) method. The research was conducted in two cycles, consisting of planning, implementation, observation, and reflection stages, involving 30 students as research subjects. Data were collected through writing tests, observation sheets, motivation questionnaires, and field notes, then analyzed using descriptive qualitative and quantitative approaches. The results revealed an increase in the average writing score from 66.7 to 81.2 after the intervention, with the paired t-test results (t = 93.48; p < 0.001) indicating a statistically significant difference. These findings demonstrate that the classroom action method is effective in enhancing students’ writing skills, learning motivation, and active participation. The study recommends implementing interactive, reflective, and collaborative learning strategies to improve the quality of writing instruction in junior high schools.